Synthesis of cis-1,2-diol-type chiral ligands and their dioxaborinane derivatives: Application for the asymmetric transfer hydrogenation of various ketones and biological evaluation - Kılıç, Ahmet; Balcı, Tuğba Ersayan; Arslan, Nevin; Aydemir, Murat; Durap, Feyyaz; Okumuş, Veysi; Tekin, Recep (Wıley, 2020)
Two cis-1,2-diol-type chiral ligands (T1 and T2) and their tri-coordinated chiral dioxaborinane (T(1–2)B(1–2)) and four-coordinated chiral dioxaborinane adducts with 4-tert-butyl pyridine sustained by N ! B dative bonds (T(1–2)B(1–2)-N) were synthesized and characterized by various spectroscopic techniques such as NMR (1 H, 13C, and 11B), FT-IR and UV–Vis spectroscopy, LC–MS/MS, and elemental analysis. It was suggested that both ferrocene and trifluoromethyl groups played key roles in the catalytic and biological studies because they could tune the solubility of the chiral dioxaborinane complexes and adjust the strength of intermolecular interactions. To assess the biological activities of newly synthesized chiral dioxaborinane compounds, DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging, reducing power, antibacterial, DNA binding, and DNA cleavage activities were tested. Then, all chiral dioxaborinane complexes were investigated as catalysts for the asymmetric transfer hydrogenation of various ketones under suitable conditions. The results indicated that the chiral dioxaborinane catalysts performed well with high yields.
Keywords: Asymmetric transfer hydrogenation; Biological activitieschiral dioxaborinanesCis-1; 2-diol-type chiral ligands